Cortical activation pattern during shoulder simple versus vibration exercises： a functional near infrared spectroscopy study - Jang, SungHo; Yeo, SangSeok; Lee, SeungHyun; Jin, SangHyun; Lee, MiYoung (Neural regeneration research, 2017)
To date, the cortical effect of exercise has not been fully elucidated. Using the functional near infrared spectroscopy, we attempted to compare the cortical effect between shoulder vibration exercise and shoulder simple exercise. Eight healthy subjects were recruited for this study. Two different exercise tasks（shoulder vibration exercise using the flexible pole and shoulder simple exercise） were performed using a block paradigm. We measured the values of oxygenated hemoglobin in the four regions of interest： the primary sensory-motor cortex（SM1 total, arm somatotopy, and leg and trunk somatotopy）, the premotor cortex, the supplementary motor area, and the prefrontal cortex. During shoulder vibration exercise and shoulder simple exercise, cortical activation was observed in SM1（total, arm somatotopy, and leg and trunk somatotopy）, premotor cortex, supplementary motor area, and prefrontal cortex. Higher oxygenated hemoglobin values were also observed in the areas of arm somatotopy of SM1 compared with those of other regions of interest. However, no significant difference in the arm somatotopy of SM1 was observed between the two exercises. By contrast, in the leg and trunk somatotopy of SM1, shoulder vibration exercise led to a significantly higher oxy-hemoglobin value than shoulder simple exercise. These two exercises may result in cortical activation effects for the motor areas relevant to the shoulder exercise, especially in the arm somatotopy of SM1. However, shoulder vibration exercise has an additional cortical activation effect for the leg and trunk somatotopy of SM1.